Sol as well as preparation method and application thereof
By forming a raspberry-like structural coating with TiO2 sol particles attached to the SiO2 microsphere matrix on the photovoltaic glass, the problem of efficiency reduction caused by pollution of photovoltaic modules is solved, self-cleaning and photodegradation effects are achieved, and the stability of the module is improved. and power generation efficiency.
Patent Information
- Application Number
- CN202411370648.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-10
AI Technical Summary
Photovoltaic modules have reduced efficiency due to surface pollution in urban environments, and it is difficult for the existing technology to maintain cleanliness and efficient power generation for a long time.
A raspberry-like structure coating with TiO2 sol particles attached to the SiO2 microsphere matrix is used to degrade organic matter by photocatalyzing and without residue after rainwater erosion, forming a self-cleaning film layer.
Effectively degrade surface organic matter, keep photovoltaic glass clean, improve light transmittance and power generation efficiency, extend service life and reduce maintenance costs.
Smart Images

Figure BDA0005068882380000201 
Figure BDA0005068882380000211
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic components, and in particular relates to a sol and a preparation method and application thereof. Background Art
[0002] With the global economic growth and the development of clean energy, the photovoltaic industry, as a representative of clean energy, has increased its cumulative installed capacity by 25 times in the past decade. The rapid development of the photovoltaic industry has led to the oversaturation of solar photovoltaic module production capacity, and has gradually shifted from large-scale centralized distribution to small-scale decentralized layout, such as building roofs, viaduct sound barriers and solar roads. There are obvious differences between solid suspended particles in nature and urban roads. Solid suspended particles in urban roads usually combine with hydrocarbons, nitrogen oxides, sulfur oxides, etc. emitted by automobile exhaust to form organic solid suspended particles. Photovoltaic modules that have been operating for a long time in such an environment usually accumulate a layer of powder formed by organic solid suspended particles on the surface, resulting in a significant decrease in the transmittance of the coated glass on the module. Due to the particularity of solid particles, rainwater is difficult to play an effective cleaning role. Organic matter remains on the surface of the coated glass, and the photoelectric conversion efficiency of the module also decreases, seriously affecting the normal power generation of the module.
[0003] In the related art, CN104588021B discloses a TiO 2 The preparation method and application of the photocatalytic coating is to prepare a layer of inert porous nano-SiO2 with strong bonding force on a foam metal substrate by electro-depositing an organic silane gel sol precursor solution. 2 The middle layer is then loaded with anatase nano-TiO 2 The coating is finally prepared into a composite coating material with high photocatalytic activity, which is used for photocatalytic degradation of organic pollutants in air or sewage. 2 The intermediate layer overcomes the problem of SiO 2 The film thickness in the middle layer is not high, the porosity is not enough, and the TiO 2 The method has the advantages of low loading capacity, poor bonding with the substrate, and the thickness of the intermediate layer is adjustable, which has better bonding with the substrate, increasing the loading capacity while enhancing the bonding with the subsequent loading coating, greatly improving the photocatalytic activity. This method is simple to operate, low in cost, and high in reusability, and is expected to be widely used in industrial production. However, SiO prepared by electrodeposition 2 The intermediate layer cannot overcome the problem of long-term weather resistance. CN101306838B provides a highly stable neutral mixed crystal nano-TiO 2The invention discloses a method for preparing a hydrosol, which belongs to the technical field of photocatalytic active nano titanium dioxide material preparation process. The method of the invention comprises the following main steps: (1) hydrolyzing and precipitating a titanium compound with an alkaline solution, filtering, and washing; (2) adding an acid solution, degumming at 60-100°C, and adding a certain amount of SiO2 sol as a stabilizer and a metal salt as a dopant, and continuing the reaction for a period of time; (3) adding an alkaline solution to adjust the pH value of the solution to 7-8; (4) filtering, washing, dissolving the filter cake in a certain amount of water, and redispersing, and finally obtaining a stable neutral mixed crystal nano TiO 2 The TiO prepared by the present invention 2 The composite hydrosol is neutral, has good transparency and stability, has a controllable ratio of anatase and rutile crystal forms, and has a wide spectral response range. 2 The hydrosol spraying operation is convenient. The hydrosol can use solar energy for sewage treatment, air purification, antibacterial treatment, glass coating treatment, etc. However, neutral TiO 2 The composite hydrosol has poor bonding with the glass substrate, and the film layer formed by spraying is difficult to use for a long time. 2 The coating structure comprises a substrate and a nano-TiO2 coating loaded on the surface of the substrate. 2 A method for preparing a coating structure, wherein a linear titanium oxide polymer solution is used to coat a substrate material, and then dried and sintered to obtain a substrate material loaded with nano-TiO 2 The coating structure of the nano-TiO prepared by the linear titanium oxide polymer 2 The coating structure has excellent photocatalytic effect and super hydrophilic effect, and thus has broad application prospects in the fields of air purification, water treatment, deodorization, antibacterial, antifouling, self-cleaning, etc. 2 The coating does not have a loose and porous structure and the transmittance is usually very low.
[0004] Therefore, it is still necessary to develop a new material or method to solve the current problem of reduced efficiency of photovoltaic modules due to surface contamination. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a sol, which, when used in photovoltaic glass, forms a TiO 2 -SiO 2 The film layer can degrade organic matter in contact with its surface, and no organic matter remains after being rinsed with water, which gives the photovoltaic glass good self-cleaning and photodegradation properties of organic matter.
[0006] The invention also provides a method for preparing the sol.
[0007] The invention also provides an organic matter degradation film.
[0008] The invention also provides a photovoltaic glass.
[0009] The first aspect of the present invention provides a sol, wherein secondary particles are dispersed in the sol, and the secondary particles include SiO 2 Microsphere substrate and attached to the SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, the TiO 2 The average particle size of the sol particles is smaller than that of the SiO 2 The average particle size of the microsphere matrix.
[0010] One of the technical solutions of the present invention regarding the sol has at least the following beneficial effects:
[0011] The anti-reflection film layer of traditional photovoltaic glass generally has the property of being oleophilic on the surface, which is easily contaminated by organic matter and difficult to be washed away by rainwater. After drying, the organic matter becomes spots adhering to the glass, which greatly reduces the transmittance of the coated glass in this area. The sol of the present invention aims to solve the pollution of organic solid particles to photovoltaic coated glass, thereby maintaining the normal power generation of photovoltaic modules. Specifically, the sol of the present invention is dispersed with secondary particles, and the secondary particles include SiO 2 Microsphere substrate and attached to the SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, the TiO 2 The average particle size of the sol particles is smaller than that of the SiO 2 Average particle size of microsphere matrix. TiO 2 Sol particles in SiO 2 TiO formed on the surface of microsphere substrate 2 -SiO 2 The raspberry-like structure is coated on the surface of photovoltaic glass. As the glass is tempered, the TiO 2 -SiO 2 The raspberry-like structure and the bonding characteristics of Si-O and Ti-O form TiO 2 Only a few are transformed into rutile, and more anatase TiO is retained. 2 , which is conducive to the super-hydrophilic and photocatalytic oxidation of organic matter under light. 2 -SiO 2The film layer can more fully contact and degrade organic matter on its surface, and no organic matter remains after being washed with water, giving photovoltaic glass good self-cleaning and photodegradation properties of organic matter. Organic matter on the film surface of photovoltaic modules can be effectively removed after being exposed to sunlight and washed by rain, keeping the film surface clean, and enabling photovoltaic modules to maintain stable power generation efficiency for a long time in an environment full of organic solid suspended particles.
[0012] According to some embodiments of the present invention, the average particle size of the secondary particles is 70 nm to 80 nm.
[0013] According to some embodiments of the present invention, the average particle size of the secondary particles is any one of 70nm, 71nm, 72nm, 73nm, 74nm, 75nm, 76nm, 77nm, 78nm, 79nm, and 80nm, or a range formed by any two of them.
[0014] According to some embodiments of the present invention, the TiO 2 The average particle size of the sol particles is 15nm to 20nm.
[0015] According to some embodiments of the present invention, the TiO 2 The average particle size of the sol particles is any one of 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, and 20 nm, or a value in a range formed by any two of them.
[0016] According to some embodiments of the present invention, the SiO 2 The average particle size of the microsphere matrix is 40nm to 60nm.
[0017] According to some embodiments of the present invention, the SiO 2 The average particle size of the microsphere substrate is any one of 40 nm, 45 nm, 50 nm, 55 nm, and 60 nm, or a range formed by any two of them.
[0018] A second aspect of the present invention provides a method for preparing a sol, comprising the following steps:
[0019] (1) Premixing butyl titanate, a diluent and acetic acid to prepare liquid A;
[0020] (2) mixing water and a diluent, and adding a pH adjuster to adjust the pH to obtain a solution B;
[0021] (3) Add the A solution dropwise to the stirred B solution and continue stirring to react to obtain nano-TiO 2 Sol;
[0022] (4) The TiO 2 Sol and SiO 2The coating solutions are mixed to obtain the sol.
[0023] A technical solution in the method for preparing sol of the present invention has at least the following beneficial effects:
[0024] The sol preparation process of the present invention is simple, easy to use, highly compatible, and highly stable, and is suitable for large-scale industrial production. It can give photovoltaic glass good self-cleaning and photodegradation properties of organic matter, greatly extending the service life of photovoltaic glass and reducing the maintenance cost of photovoltaic glass.
[0025] In step (1), ethanol is used to disperse butyl titanate, and acetic acid is added to control the reaction between butyl titanate and water in the air.
[0026] In step (2), water is dispersed and pH is adjusted in order to control the speed of the hydrolysis reaction.
[0027] In step (3), the purpose is to allow butyl titanate to fully react with water.
[0028] The purpose of step (4) is to make TiO 2 Sol-SiO in coating solution 2 A special raspberry-like structure is formed on the surface of the microspheres.
[0029] According to some embodiments of the present invention, in step (1), the molar ratio of butyl titanate, diluent and acetic acid is 1:20-30:0.25-0.75.
[0030] According to some embodiments of the present invention, in step (2), the mass ratio of the water to the diluent is 1:25-35.
[0031] According to some embodiments of the present invention, in step (2), the molar ratio of the water to the butyl titanate is 2 to 5:1.
[0032] According to some embodiments of the present invention, in step (2), the pH is adjusted to 2-3.
[0033] According to some embodiments of the present invention, in step (3), the dropping speed is 2 to 4 s / drop.
[0034] According to some embodiments of the present invention, in step (3), the stirring reaction time is 3 to 5 hours.
[0035] In step (3), liquid A is added dropwise to liquid B in order to allow butyl titanate to be fully hydrolyzed in excess water to form a uniform nanosol. If liquid B is added to liquid A, butyl titanate will hydrolyze quickly, especially when the amount of acetic acid added is small. Excessive butyl titanate will compete with water to react, resulting in insufficient hydrolysis of part of butyl titanate, making it difficult to form a sol with uniform particles.
[0036] In the present invention, TiO 2 The sol does not need to be heated or aged and can be directly added to the target solution for use.
[0037] According to some embodiments of the present invention, in step (4), the TiO 2 Sol and SiO 2 The solid content ratio of the plating solution is 0.03-0.05:1.
[0038] The third aspect of the present invention provides an organic matter degradation film, which is obtained by solidifying the sol of the first aspect of the present invention or the sol prepared by the method of the second aspect.
[0039] One of the technical solutions of the present invention regarding the organic degradation film has at least the following beneficial effects:
[0040] First, by introducing TiO 2 -SiO 2 The raspberry-like structure of TiO enhances the degradation performance of the film layer on organic matter. 2 It can play a photocatalytic role under light conditions and degrade organic matter into harmless substances. Moreover, after this film layer is formed on the surface of photovoltaic glass, it will not leave any organic residue after being washed by rainwater, and it has self-cleaning properties, avoiding the problem that traditional film layers are easily contaminated with oil. For photovoltaic modules, this feature is particularly important because it can effectively prevent organic pollutants from accumulating on the surface of the glass, thereby affecting the transmittance and power generation efficiency. Whether in an environment with severe air pollution or a large number of suspended organic particles, this film layer can keep the glass surface clean for a long time, ensuring the continuous and efficient power generation of photovoltaic modules. This degradation film combines the two core advantages of self-cleaning and photodegradation, significantly improving the practicality and reliability of photovoltaic glass, and is especially suitable for occasions that require maintenance of high transmittance and self-cleaning functions.
[0041] The fourth aspect of the present invention provides a photovoltaic glass, on the surface of which the organic degradation film according to the third aspect of the present invention is provided.
[0042] One of the technical solutions of the present invention regarding photovoltaic glass has at least the following beneficial effects:
[0043] Self-cleaning function: The organic degradation film on the surface of the photovoltaic glass has self-cleaning properties and can completely remove the attached organic matter after being washed by rainwater, avoiding the problem of dust and organic pollutants easily accumulating on the surface of traditional photovoltaic glass, thereby reducing the frequency of manual cleaning and maintenance costs.
[0044] Photodegradation of organic matter: The degradation film contains TiO 2 Particles, TiO2 Under sunlight, it can produce a photocatalytic reaction, effectively degrading organic matter attached to the glass surface. Even in dry conditions, photocatalytic degradation can still work, ensuring that the glass surface remains clean for a long time.
[0045] Improve light transmittance and stabilize power generation efficiency: Since the degradation film can effectively remove organic matter and pollutants, maintain the high light transmittance of photovoltaic glass, and ensure that sunlight can smoothly pass through the glass into the photovoltaic cell layer, thereby maximizing the power generation efficiency of photovoltaic modules. In long-term use, this photovoltaic glass can better maintain stable power generation performance and reduce the efficiency drop caused by the accumulation of pollutants.
[0046] Durability and chemical stability: TiO in degradation films 2 -SiO 2 The raspberry-like structure forms a stable film layer by bonding with the glass, which has good weather resistance and chemical stability. This allows the photovoltaic glass to be used for a long time in various climatic conditions, maintain good performance, and is not easily invalidated by environmental influences.
[0047] Reduce pollution from organic solid suspended particles: In industrial or urban environments with a lot of organic matter, the photovoltaic glass effectively prevents the accumulation of organic matter on the glass surface through the self-cleaning and photodegradation properties of the degradation film, ensuring the long-term and efficient power generation capacity of photovoltaic modules in such environments.
[0048] In summary, this photovoltaic glass not only improves the power generation efficiency of the photovoltaic system, but also reduces maintenance costs and cleaning difficulties. It also has good weather resistance and long-term stability, and is particularly suitable for use in environments with severe pollution. DETAILED DESCRIPTION
[0049] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0050] In the first aspect, some embodiments of the present invention provide a sol in which secondary particles are dispersed, and the secondary particles include SiO 2 Microsphere substrate and attached to SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, TiO 2 The average particle size of sol particles is smaller than that of SiO 2 The average particle size of the microsphere matrix.
[0051] It is understandable that the anti-reflection film layer of traditional photovoltaic glass generally has the property of being oleophilic on the surface, which is easily contaminated with organic matter and difficult to be washed away by rainwater. After drying, the organic matter becomes spots adhering to the glass, which greatly reduces the transmittance of the coated glass in this area. The sol of the present invention is intended to solve the pollution of organic solid particles to photovoltaic coated glass, thereby maintaining the normal power generation of photovoltaic modules. Specifically, the sol of the present invention is dispersed with secondary particles, which include SiO 2 Microsphere substrate and attached to SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, TiO 2 The average particle size of sol particles is smaller than that of SiO 2 Average particle size of microsphere matrix. TiO 2 Sol particles in SiO 2 TiO formed on the surface of microsphere substrate 2 -SiO 2 The raspberry-like structure is coated on the surface of photovoltaic glass. As the glass is tempered, the TiO 2 -SiO 2 The raspberry-like structure and the bonding characteristics of Si-O and Ti-O form TiO 2 Only a few are transformed into rutile, and more anatase TiO is retained. 2 The test results show that it is beneficial to produce super hydrophilicity and photocatalytic oxidation of organic matter under light. The TiO 2 -SiO 2 The film layer can more fully contact and degrade organic matter on its surface, and no organic matter remains after being washed with water, giving photovoltaic glass good self-cleaning and photodegradation properties of organic matter. Organic matter on the film surface of photovoltaic modules can be effectively removed after being exposed to sunlight and washed by rain, keeping the film surface clean, and enabling photovoltaic modules to maintain stable power generation efficiency for a long time in an environment full of organic solid suspended particles.
[0052] In combination with the first aspect, in some embodiments of the present invention, the average particle size of the secondary particles is 70 nm to 80 nm.
[0053] In combination with the first aspect, in some embodiments of the present invention, the average particle size of the secondary particles is any value among 70nm, 71nm, 72nm, 73nm, 74nm, 75nm, 76nm, 77nm, 78nm, 79nm, 80nm or a range value formed by any two of them.
[0054] In combination with the first aspect, in some embodiments of the present invention, TiO 2 The average particle size of the sol particles is 15nm to 20nm.
[0055] In combination with the first aspect, in some embodiments of the present invention, TiO 2 The average particle size of the sol particles is any one of 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, and 20 nm, or a value in a range formed by any two of them.
[0056] In combination with the first aspect, in some embodiments of the present invention, SiO 2 The average particle size of the microsphere matrix is 40nm to 60nm.
[0057] In combination with the first aspect, in some embodiments of the present invention, SiO 2 The average particle size of the microsphere substrate is any one of 40 nm, 45 nm, 50 nm, 55 nm, and 60 nm, or a range formed by any two of them.
[0058] In a second aspect, in some embodiments of the present invention, there is provided a method for preparing a sol, comprising the following steps:
[0059] (1) Premixing butyl titanate, a diluent and acetic acid to prepare liquid A;
[0060] (2) mixing water and a diluent, and adding a pH adjuster to adjust the pH to obtain a solution B;
[0061] (3) Add liquid A dropwise to the stirring liquid B and continue stirring to produce nano-TiO 2 Sol;
[0062] (4) TiO 2 Sol and SiO 2 The coating solutions are mixed to obtain a sol.
[0063] It can be understood that the sol preparation process in the present invention is simple, easy to use, highly compatible, and highly stable, and is suitable for large-scale industrial production. It can give photovoltaic glass good self-cleaning and photodegradation properties of organic matter, greatly extending the service life of photovoltaic glass and reducing the maintenance cost of photovoltaic glass.
[0064] In step (1), ethanol is used to disperse butyl titanate, and acetic acid is added to control the reaction between butyl titanate and water in the air.
[0065] In step (2), water is dispersed and pH is adjusted in order to control the speed of the hydrolysis reaction.
[0066] In step (3), the purpose is to allow butyl titanate to fully react with water.
[0067] The purpose of step (4) is to make TiO 2 Sol-SiO in coating solution 2 A special raspberry-like structure is formed on the surface of the microspheres.
[0068] In combination with the second aspect, in some embodiments of the present invention, in step (1), the molar ratio of butyl titanate, diluent and acetic acid is 1:20-30:0.25-0.75.
[0069] In combination with the second aspect, in some embodiments of the present invention, in step (2), the mass ratio of water to diluent is 1:25-35.
[0070] In combination with the second aspect, in some embodiments of the present invention, in step (2), the molar ratio of water to butyl titanate is 2 to 5:1.
[0071] In combination with the second aspect, in some embodiments of the present invention, the diluent is methanol, ethanol, isopropanol or n-butanol.
[0072] In combination with the second aspect, in some embodiments of the present invention, in step (2), the pH is adjusted to 2-3.
[0073] In combination with the second aspect, in some embodiments of the present invention, in step (2), the pH adjuster is 0.2 mol / L hydrochloric acid or 1.6 mol / L nitric acid.
[0074] In combination with the second aspect, in some embodiments of the present invention, in step (3), the dripping speed is 2 to 4 s / drop.
[0075] In combination with the second aspect, in some embodiments of the present invention, in step (3), the stirring reaction time is 3 to 5 hours.
[0076] In step (3), liquid A is added dropwise to liquid B in order to allow butyl titanate to be fully hydrolyzed in excess water to form a uniform nanosol. If liquid B is added to liquid A, butyl titanate will hydrolyze quickly, especially when the amount of acetic acid added is small. Excessive butyl titanate will compete with water to react, resulting in insufficient hydrolysis of part of butyl titanate, making it difficult to form a sol with uniform particles.
[0077] In the present invention, TiO 2 The sol does not need to be heated or aged and can be directly added to the target solution for use.
[0078] In combination with the second aspect, in some embodiments of the present invention, in step (4), TiO 2 Sol and SiO 2 The solid content ratio of the plating solution is 0.03-0.05:1.
[0079] It should be noted that TiO 2 Sol and SiO 2 Coating solution (mainly SiO 2The average particle size of the former (15-20nm) was smaller than that of the coating solution (40-60nm) by laser particle size meter. After mixing them, the initial test obtained a distribution curve of different particle sizes. However, after aging for more than 12 hours, the color of the coating solution became darker, and the average particle size was higher than that of the single coating solution (70-80nm), and the distribution of small particle size was significantly reduced, which shows that TiO 2 The sol is attached to the SiO 2 Large particles are formed on the surface of the microspheres, and this structure is similar to a raspberry structure. The raspberry structure is "small balls sticking to big balls", TiO 2 The sol has a larger specific surface area and can contact the pollutants more effectively after forming a film layer, and play a role in photocatalytic degradation of organic matter.
[0080] In step (4), SiO 2 The preparation method of the coating solution can be:
[0081] a. Prepare the polystyrene core by soap-free emulsion polymerization: put the comonomer and water in a reaction vessel, add styrene, raise the temperature to 50-85°C under nitrogen protection, and add the initiator aqueous solution dropwise to react to obtain a cationic polystyrene emulsion;
[0082] Wherein, the comonomer is a quaternized vinyl monomer and / or an amino-containing vinyl monomer; the quaternized vinyl monomer is selected from one or more of acryloyloxyethyl trimethoxy ammonium chloride, methacryloyloxyethyl trimethyl ammonium chloride, (meth)acrylamidopropyl trimethyl ammonium chloride, or diallyl dimethyl ammonium chloride; the amino-containing vinyl monomer is selected from one or more of dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, or diisopropylaminoethyl (meth)acrylate, wherein when the comonomer is an amino-containing vinyl monomer, the amino-containing vinyl monomer needs to be protonated with an acid before performing step (1), and the acid is selected from an inorganic acid or an organic acid;
[0083] b. Preparation of silica-coated polystyrene core-shell microsphere emulsion: The cationic polystyrene emulsion as a hard template is mixed with a solvent, and a silicon source is added to react under stirring at 15-35°C to obtain SiO 2 Coating solution.
[0084] Among them, the inorganic acid is hydrochloric acid, sulfuric acid, nitric acid or phosphoric acid, and the organic acid is acetic acid, citric acid or oxalic acid.
[0085] The required amount of the inorganic acid is calculated as monobasic acid, and the molar ratio of the acid to the amino group contained in the amino group-containing vinyl monomer is 50-100%.
[0086] The silicon source material is selected from one or more of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane or γ-(methacryloyloxy)propyltrimethoxysilane.
[0087] The initiator is potassium persulfate or azobisisobutylamidine hydrochloride.
[0088] In step a, the mass ratio of the comonomer to styrene is 0.5-4:10-20. The mass ratios of the comonomer, styrene, initiator and water in the whole system are: 0.5-4% of the comonomer, 10-20% of styrene, 0.1-1% of the initiator and 75-89.4% of water.
[0089] In step b, the amount of solvent used is based on diluting the cationic polystyrene emulsion to a solid content of 1-20% by mass. The mass ratio of the solid mass of the polystyrene emulsion to the amount of silicon source added is 10-30%. The solvent is one or more of water, methanol, ethanol, ethylene glycol, n-propanol, isopropanol, propylene glycol, glycerol, n-butanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol methyl ether, propylene glycol butyl ether, tripropylene glycol monomethyl ether or tripropylene glycol monoethyl ether.
[0090] In step a, after adding styrene, stirring is performed at a stirring speed of 150-500 rpm. The initiator is added dropwise at a dropping speed of 0.1-2 mL / min.
[0091] In terms of weight percentage, the above hydroxyl-containing silica-alumina sol and nano-core-shell SiO 2 The volume ratio of the microsphere sol raw materials is 1:1-10. Among them, the volume ratio of the raw materials is 1:4-10. The hydroxy-containing silicon aluminum sol raw materials are obtained by reacting raw materials containing water, an acidic catalyst, a solvent, an aluminum salt and a silicon source material, wherein the mass of the aluminum salt is 0.025-0.1g relative to the volume of 1mL of the silicon source material. Relative to the volume of 1mL of the silicon source material, the solvent content is 1-20mL, the water content is 0.1-1mL, the catalyst content is 0.01-0.1mL, and the catalyst is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, acetic acid, citric acid and oxalic acid. The silicon source material added when preparing the hydroxy-containing silica-alumina sol is one or more of tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane or γ-(methacryloyloxy)propyltrimethoxysilane.
[0092] In a third aspect, some embodiments of the present invention provide an organic degradation film, which is obtained by curing the sol of the first aspect of the present invention or the sol prepared by the method of the second aspect.
[0093] It can be understood that, firstly, by introducing TiO 2 -SiO 2 The raspberry-like structure of TiO enhances the degradation performance of the film layer on organic matter. 2 It can play a photocatalytic role under light conditions and degrade organic matter into harmless substances. Moreover, after this film layer is formed on the surface of photovoltaic glass, it will not leave any organic residue after being washed by rainwater, and it has self-cleaning properties, avoiding the problem that traditional film layers are easily contaminated with oil. For photovoltaic modules, this feature is particularly important because it can effectively prevent organic pollutants from accumulating on the surface of the glass, thereby affecting the transmittance and power generation efficiency. Whether in an environment with severe air pollution or a large number of suspended organic particles, this film layer can keep the glass surface clean for a long time, ensuring the continuous and efficient power generation of photovoltaic modules. This degradation film combines the two core advantages of self-cleaning and photodegradation, significantly improving the practicality and reliability of photovoltaic glass, and is especially suitable for occasions that require maintenance of high transmittance and self-cleaning functions.
[0094] In a fourth aspect, in some embodiments of the present invention, a photovoltaic glass is provided, on the surface of which the organic degradation film according to the third aspect of the present invention is provided.
[0095] It can be understood that one of the technical solutions of the photovoltaic glass of the present invention has at least the following beneficial effects:
[0096] Self-cleaning function: The organic degradation film on the surface of the photovoltaic glass has self-cleaning properties and can completely remove the attached organic matter after being washed by rainwater, avoiding the problem of dust and organic pollutants easily accumulating on the surface of traditional photovoltaic glass, thereby reducing the frequency of manual cleaning and maintenance costs.
[0097] Photodegradation of organic matter: The degradation film contains TiO 2 Particles, TiO 2 Under sunlight, it can produce a photocatalytic reaction, effectively degrading organic matter attached to the glass surface. Even in dry conditions, photocatalytic degradation can still work, ensuring that the glass surface remains clean for a long time.
[0098] Improve light transmittance and stabilize power generation efficiency: Since the degradation film can effectively remove organic matter and pollutants, maintain the high light transmittance of photovoltaic glass, and ensure that sunlight can smoothly pass through the glass into the photovoltaic cell layer, thereby maximizing the power generation efficiency of photovoltaic modules. In long-term use, this photovoltaic glass can better maintain stable power generation performance and reduce the efficiency drop caused by the accumulation of pollutants.
[0099] Durability and chemical stability: TiO in degradation films 2 -SiO 2 The raspberry-like structure forms a stable film layer by bonding with the glass, which has good weather resistance and chemical stability. This allows the photovoltaic glass to be used for a long time in various climatic conditions, maintain good performance, and is not easily invalidated by environmental influences.
[0100] Reduce pollution from organic solid suspended particles: In industrial or urban environments with a lot of organic matter, the photovoltaic glass effectively prevents the accumulation of organic matter on the glass surface through the self-cleaning and photodegradation properties of the degradation film, ensuring the long-term and efficient power generation capacity of photovoltaic modules in such environments.
[0101] In summary, this photovoltaic glass not only improves the power generation efficiency of the photovoltaic system, but also reduces maintenance costs and cleaning difficulties. It also has good weather resistance and long-term stability, and is particularly suitable for use in environments with severe pollution.
[0102] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0103] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0104] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0105] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0106] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0107] The core raw materials of the purchased coating solution A in the comparative example were purchased from Covestro Polymer (China) Co., Ltd., model ART5B.
[0108] Coating solution B, its core raw materials were purchased from Xibenkang High-tech Materials Co., Ltd., model: 860.
[0109] The core raw materials of the purchased coating solution C were purchased from Jiaxing Haote New Material Technology Co., Ltd., model: 3-570.
[0110] Example 1
[0111] A sol is prepared, in which secondary particles are dispersed, and the secondary particles include SiO 2 Microsphere substrate and attached to SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, TiO 2 The average particle size of sol particles is smaller than that of SiO 2 The average particle size of the microsphere matrix. Specifically, the average particle size of the secondary particles is 76nm, and the average particle size of TiO 2 The average particle size of the sol particles is 16nm. 2 The average particle size of the microsphere matrix is 48 nm.
[0112] The specific preparation method is:
[0113] (1) Add 25 g of ethanol, 0.6 g of acetic acid, and 6.8 g of butyl titanate to a beaker with a magnetic stirrer, stir for 10 min, and then transfer to a constant pressure funnel;
[0114] (2) Add 1.08 g of purified water, 30 g of ethanol and 0.4 g of nitric acid solution to a conical flask with a magnetic stirrer, then connect the constant pressure funnel in (1) to the top of the conical flask, and control the drop rate to 2 to 4 seconds per drop. After the drop addition is completed, continue stirring and reacting at room temperature for 4 hours to obtain TiO with a solid content of 4.2 wt.%. 2 Sol;
[0115] (3) TiO 2 Sol and SiO 2 The plating solutions were mixed at a solid content ratio of 0.04:1 to prepare the sol of Example 1.
[0116] It should be noted that TiO 2 Sol and SiO 2 Coating solution (mainly SiO 2 The average particle size of the former (15-20nm) was smaller than that of the coating solution (40-60nm) by laser particle size meter. After mixing them, the initial test obtained a distribution curve of different particle sizes. However, after aging for more than 12 hours, the color of the coating solution became darker, and the average particle size was higher than that of the single coating solution (70-80nm), and the distribution of small particle size was significantly reduced, which shows that TiO2 The sol is attached to the SiO 2 Large particles are formed on the surface of the microspheres, and this structure is similar to a raspberry structure. The raspberry structure is "small balls sticking to big balls", TiO 2 The sol has a larger specific surface area and can contact the pollutants more effectively after forming a film layer, and play a role in photocatalytic degradation of organic matter.
[0117] SiO 2 The preparation method of the coating solution is:
[0118] (I) Preparation of Nano-core-shell SiO 2 Microsphere sol
[0119] (1) Prepare PS core by soap-free emulsion polymerization. Weigh acryloyloxyethyl trimethoxy ammonium chloride as a comonomer and 100 mL of water and place them in a 250 mL four-necked flask. Add styrene under mechanical stirring and stir for 30 min at a stirring speed of 150 rpm. Under nitrogen protection, heat to 50°C and add an aqueous solution of initiator KPS (potassium persulfate) dropwise at a rate of 2.0 ml / min. The reaction is continued for 20 h to obtain a stable cationic polystyrene emulsion with an average particle size of 270 nm and a solid content of 10%.
[0120] The mass proportions of the comonomer, styrene monomer, initiator and water in the whole system are 0.5% of the comonomer, 10% of styrene, 0.1% of the initiator and 89.4% of the water respectively.
[0121] The particle size of the polystyrene particles in the polystyrene emulsion is measured by a Zeta ZS90 laser particle size analyzer produced by Malvern.
[0122] (2) The cationic polystyrene emulsion and the solvent methanol are mixed evenly, and the polystyrene emulsion is diluted to a solid content of 5% by mass. Under stirring at 15° C., the silicon source substance tetramethoxysilane is slowly added dropwise thereto so that the solid mass of the polystyrene emulsion is 10% relative to the mass ratio of the silicon source substance. The reaction is carried out for 3 hours to obtain a silicon dioxide-coated polystyrene nano-core-shell structure microsphere emulsion.
[0123] The residual solid content was measured to be about 16% by weight after heating and drying at 150°C for 2 hours.
[0124] (II) Method for preparing hydroxyl-rich silica sol
[0125] (1) Add 100 mL of solvent methanol into a three-necked flask, and slowly add deionized water and catalyst nitric acid mixed evenly into the three-necked flask under stirring at 15°C, and continue stirring for 30 minutes to obtain liquid A;
[0126] (2) Under stirring conditions at 15°C, aluminum salt aluminum nitrate and tetraethoxysilane as a silicon source are added to liquid A respectively, the temperature is raised to 40°C and stirring is continued for 0.5 h, then stirring is stopped and the liquid is aged at 25°C for 1 day. After cooling, a hydroxyl-rich silica-alumina sol is obtained, the solid content of which is measured to be 15 wt% (residual solid content after heating and drying at 150°C for 2 hours).
[0127] In the above process of preparing the hydroxyl-rich silica sol, the usage ratio of the solvent, deionized water, acid, aluminum salt and alkoxysilane is 1 mL: 0.1 mL: 0.01 mL: 0.025 g: 1 mL.
[0128] (III) Preparation of SiO 2 Coating solution
[0129] 100 mL of the above hydroxyl-rich silica-alumina sol was added to a three-necked flask and stirred at 15°C. 2 The microsphere sol was slowly added into the three-necked flask and stirred for 0.5 h, then the stirring was stopped to obtain the PS@SiO 2 Nano-core-shell SiO 2 Coating solution.
[0130] Among them, the above-mentioned hydroxyl-rich silica sol and nano core-shell SiO 2 The volume ratio of the microsphere sol is 1:1.
[0131] Finally, the sol of Example 1 was coated on the photovoltaic glass by roller coating, and then baked and cured at 160° C., and then tempered at 680-710° C. to obtain the anti-reflection coated glass.
[0132] Example 2
[0133] A sol is prepared, in which secondary particles are dispersed, and the secondary particles include SiO 2 Microsphere substrate and attached to SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, TiO 2 The average particle size of sol particles is smaller than that of SiO 2 The average particle size of the microsphere matrix. Specifically, the average particle size of the secondary particles is 80nm, and the average particle size of TiO 2 The average particle size of the sol particles is 20nm. 2 The average particle size of the microsphere matrix is 48 nm.
[0134] The specific preparation method is:
[0135] (1) Add 18.4 g of ethanol, 0.3 g of acetic acid, and 6.8 g of butyl titanate to a beaker with a magnetic stirrer, stir for 10 min, and then transfer to a constant pressure funnel;
[0136] (2) Add 0.72 g of purified water, 25.5 g of ethanol and 0.3 g of nitric acid solution to a conical flask with a magnetic stirrer, then connect the constant pressure funnel in (1) to the top of the conical flask, and control the drop rate to 2 to 4 seconds per drop. After the drop addition is completed, continue stirring and reacting at room temperature for 4 hours to obtain TiO with a solid content of 6.1 wt.%. 2 Sol;
[0137] (3) Take a certain amount of purchased coating solution A, and then add TiO 2 The sol and the coating solution A were mixed at a solid content ratio of 0.05:1 to obtain the sol of Example 2.
[0138] Finally, the sol of Example 2 was coated on the photovoltaic glass by roller coating, and then baked and cured at 160° C., and then tempered at 680-710° C. to obtain the anti-reflection coated glass.
[0139] Example 3
[0140] A sol is prepared, in which secondary particles are dispersed, and the secondary particles include SiO 2 Microsphere substrate and attached to SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, TiO 2 The average particle size of sol particles is smaller than that of SiO 2 The average particle size of the microsphere matrix. Specifically, the average particle size of the secondary particles is 74nm, and the average particle size of TiO 2 The average particle size of the sol particles is 15nm. 2 The average particle size of the microsphere matrix is 48 nm.
[0141] The specific preparation method is:
[0142] (1) Add 27.6 g of ethanol, 0.9 g of acetic acid, and 6.8 g of butyl titanate to a beaker with a magnetic stirrer, stir for 10 min, and then transfer to a constant pressure funnel;
[0143] (2) Add 1.8 g purified water, 45 g ethanol and 0.5 g nitric acid solution to a conical flask with a magnetic stirrer, then connect the constant pressure funnel in (1) to the top of the conical flask, and control the drop rate to 2 to 4 seconds per drop. After the drop addition is completed, continue stirring and reacting at room temperature for 4 hours to obtain TiO with a solid content of 3.2 wt.%. 2 Sol;
[0144] (3) Take a certain amount of purchased coating solution B, and then add TiO 2 The sol and the coating solution B were mixed at a solid content ratio of 0.03:1 to obtain the sol of Example 3.
[0145] Finally, the sol of Example 3 was coated on the photovoltaic glass by roller coating, and then baked and cured at 160° C., and then tempered at 680-710° C. to obtain the anti-reflection coated glass.
[0146] Example 4
[0147] A sol is prepared, in which secondary particles are dispersed, and the secondary particles include SiO 2 Microsphere substrate and attached to SiO 2 TiO on the surface of microsphere substrate 2 Sol particles, TiO 2 The average particle size of sol particles is smaller than that of SiO 2 The average particle size of the microsphere matrix. Specifically, the average particle size of the secondary particles is 76nm, and the average particle size of TiO 2 The average particle size of the sol particles is 16nm. 2 The average particle size of the microsphere matrix is 48 nm.
[0148] The specific preparation method is:
[0149] (1) Add 25 g of ethanol, 0.6 g of acetic acid, and 6.8 g of butyl titanate to a beaker with a magnetic stirrer, stir for 10 min, and then transfer to a constant pressure funnel;
[0150] (2) Add 1.08 g of purified water, 30 g of ethanol and 0.4 g of nitric acid solution to a conical flask with a magnetic stirrer, then connect the constant pressure funnel in (1) to the top of the conical flask, and control the drop rate to 2 to 4 seconds per drop. After the drop addition is completed, continue stirring and reacting at room temperature for 4 hours to obtain TiO with a solid content of 4.2 wt.%. 2 Sol;
[0151] (3) TiO 2 Sol and SiO 2 The plating solutions were mixed at a solid content ratio of 0.05:1 to prepare the sol of Example 4.
[0152] SiO 2 The preparation method of the coating solution is:
[0153] (I) Preparation of Nano-core-shell SiO 2 Microsphere sol
[0154] (1) Prepare PS core by soap-free emulsion polymerization. Weigh acryloyloxyethyl trimethoxy ammonium chloride as a comonomer and 100 mL of water and place them in a 250 mL four-necked flask. Add styrene under mechanical stirring and stir for 30 min at a stirring speed of 150 rpm. Under nitrogen protection, heat to 50°C and add an aqueous solution of initiator KPS (potassium persulfate) dropwise at a rate of 2.0 ml / min. The reaction is continued for 20 h to obtain a stable cationic polystyrene emulsion with an average particle size of 270 nm and a solid content of 10%.
[0155] The mass proportions of the comonomer, styrene monomer, initiator and water in the whole system are 0.5% of the comonomer, 10% of styrene, 0.1% of the initiator and 89.4% of the water respectively.
[0156] The particle size of the polystyrene particles in the polystyrene emulsion is measured by a Zeta ZS90 laser particle size analyzer produced by Malvern.
[0157] (2) The cationic polystyrene emulsion and the solvent methanol are mixed evenly, and the polystyrene emulsion is diluted to a solid content of 5% by mass. Under stirring at 15° C., the silicon source substance tetramethoxysilane is slowly added dropwise thereto so that the solid mass of the polystyrene emulsion is 10% relative to the mass ratio of the silicon source substance. The reaction is carried out for 3 hours to obtain a silicon dioxide-coated polystyrene nano-core-shell structure microsphere emulsion.
[0158] The residual solid content was measured to be about 16% by weight after heating and drying at 150°C for 2 hours.
[0159] (II) Method for preparing hydroxyl-rich silica sol
[0160] (1) Add 100 mL of solvent methanol into a three-necked flask, and slowly add deionized water and catalyst nitric acid mixed evenly into the three-necked flask under stirring at 15°C, and continue stirring for 30 minutes to obtain liquid A;
[0161] (2) Under stirring conditions at 15°C, aluminum salt aluminum nitrate and tetraethoxysilane as a silicon source are added to liquid A respectively, the temperature is raised to 40°C and stirring is continued for 0.5 h, then stirring is stopped and the liquid is aged at 25°C for 1 day. After cooling, a hydroxyl-rich silica-alumina sol is obtained, the solid content of which is measured to be 15 wt% (residual solid content after heating and drying at 150°C for 2 hours).
[0162] In the above process of preparing the hydroxyl-rich silica sol, the usage ratio of the solvent, deionized water, acid, aluminum salt and alkoxysilane is 1 mL: 0.1 mL: 0.01 mL: 0.025 g: 1 mL.
[0163] (III) Preparation of SiO2 Coating solution
[0164] 100 mL of the above hydroxyl-rich silica-alumina sol was added to a three-necked flask and stirred at 15°C. 2 The microsphere sol was slowly added into the three-necked flask and stirred for 0.5 h, then the stirring was stopped to obtain the PS@SiO 2 Nano-core-shell SiO 2 Coating solution.
[0165] Among them, the above-mentioned hydroxyl-rich silica sol and nano core-shell SiO 2 The volume ratio of the microsphere sol is 1:1.
[0166] Finally, the sol of Example 1 was coated on the photovoltaic glass by roller coating, and then baked and cured at 160° C., and then tempered at 680-710° C. to obtain the anti-reflection coated glass.
[0167] Comparative Example 1
[0168] The SiO in Example 1 2 The coating liquid is applied to the photovoltaic glass by roller coating, then cured by baking at 160°C, and subsequently tempered at 680-710°C to obtain the anti-reflection coated glass.
[0169] Comparative Example 2
[0170] The purchased coating liquid A is coated on the photovoltaic glass by roller coating, then baked and cured at 160°C, and then tempered at 680-710°C to obtain the anti-reflection coated glass.
[0171] Comparative Example 3
[0172] The purchased coating liquid B is coated on the photovoltaic glass by roller coating, then baked and cured at 160°C, and then tempered at 680-710°C to obtain the anti-reflection coated glass.
[0173] Comparative Example 4
[0174] The purchased coating liquid C is coated on the photovoltaic glass by roller coating, then baked and cured at 160°C, and then tempered at 680-710°C to obtain the anti-reflection coated glass.
[0175] Comparative Example 5
[0176] (1) Add 25 g of ethanol, 0.6 g of acetic acid and 6.8 g of butyl titanate to a beaker with a magnetic stirrer, stir for 10 min and transfer to a constant pressure funnel.
[0177] (2) Add 1.08 g of purified water, 30 g of ethanol and 0.4 g of nitric acid solution to a conical flask with a magnetic stirrer, then connect the constant pressure funnel in (1) to the top of the conical flask, and control the drop rate to 2 to 4 seconds per drop. After the drop addition is completed, continue stirring and reacting at room temperature for 4 hours to obtain TiO with a solid content of 4.2 wt.%. 2 Sol.
[0178] (3) Prepare SiO according to the method in Example 1 2 The coating solution is then 2 Sol and SiO 2 The plating solutions were mixed at a solid content ratio of 0.07:1 to prepare the sol of Comparative Example 5.
[0179] (4) The sol is coated on the photovoltaic glass by roller coating, and then baked and cured at 160°C, and then tempered at 680-710°C to obtain TiO 2 Anti-reflective coated glass.
[0180] Comparative Example 6
[0181] (1) Add 25 g of ethanol, 0.6 g of acetic acid and 6.8 g of butyl titanate to a beaker with a magnetic stirrer, stir for 10 min and transfer to a constant pressure funnel.
[0182] (2) Add 2.52 g of purified water, 30 g of ethanol and 0.4 g of nitric acid solution to a conical flask with a magnetic stirrer, then connect the constant pressure funnel in (1) to the top of the conical flask, and control the drop rate to 2 to 4 seconds per drop. After the drop addition is completed, continue stirring and reacting at room temperature for 4 hours to obtain TiO with a solid content of 4.2 wt.%. 2 Sol.
[0183] (3) Prepare SiO according to the method in Example 1 2 The coating solution is then 2 Sol and SiO 2 The plating solutions were mixed at a solid content ratio of 0.06:1 to prepare the sol of Comparative Example 6.
[0184] (4) The sol is coated on the photovoltaic glass by roller coating, and then baked and cured at 160°C, and then tempered at 680-710°C to obtain TiO 2 Anti-reflective coated glass.
[0185] Comparative Example 7
[0186] (1) Add 25 g of ethanol, 0.6 g of acetic acid and 6.8 g of butyl titanate to a beaker with a magnetic stirrer, stir for 10 min and transfer to a constant pressure funnel.
[0187] (2) Add 1.08 g of purified water, 30 g of ethanol and 0.4 g of nitric acid solution to a conical flask with a magnetic stirrer, then connect the constant pressure funnel in (1) to the top of the conical flask, and control the drop rate to 2 to 4 seconds per drop. After the drop addition is completed, continue stirring and reacting at room temperature for 4 hours to obtain TiO with a solid content of 4.2 wt.%. 2 Sol.
[0188] (3) Prepare SiO according to the method in Example 1 2 The coating solution is then 2 Sol and SiO 2 The plating solutions were mixed at a solid content ratio of 0.04:1 to prepare the sol of Comparative Example 7.
[0189] (4) The sol is coated on the photovoltaic glass by roller coating, and then baked and cured at 160°C, and then tempered at 500-520°C to obtain TiO 2 Anti-reflective coated glass.
[0190] Evaluation method
[0191] (1) Solid content: Weigh the solution to be measured into a beaker on a precision electronic balance and record the empty beaker weight G. 杯 and the weight of the solution measured G 液 Place the beaker containing the tested solution in a 160℃ constant temperature drying oven and dry it for 1 hour. After taking it out, transfer it to a drying dish and cool it to room temperature. Then weigh the total weight of the beaker and the solid in the cup to obtain G 杯+固 , calculate solid content = (G 杯+固 -G 杯 ) / G 液 ;
[0192] (2) Transmittance test: The transmittance of the film layer (T) is measured using the Beijing Aobote GST-3 air-floating table-top embossed glass spectral transmittance measuring instrument. The coated glass to be measured is placed with the film surface facing up on the instrument's measuring table and moved to the measuring point. When the instrument starts measuring, the glass is moved to continuously measure a total of 12 transmittance data at different positions. The maximum and minimum values are removed and the average value is taken. The transmittance enhancement (ΔT) is the measured transmittance minus the transmittance of the substrate glass.
[0193] (3) Photodecomposition of organic matter experiment: prepare a clean coated glass with a size of 100×100 mm and a clean crucible, draw a closed circle along the outer circle with an oil pen, then weigh a certain weight of 0.02wt.% methyl orange / 0.2wt.% xylenol orange solution on a 1 / 10,000 balance, tilt the glass so that the solution covers the area inside the circle, dry it at room temperature, place it under a halogen tungsten lamp for 1 hour, then use quantitative purified water to elute the methyl orange / xylenol orange in the circle, wait for the elute glass to dry, then test the transmittance in the circle, and use PerkinElmer LAMBDA 365 UV / Vis spectrophotometer to test the absorbance of methyl orange / xylenol orange in the eluate at 600nm / 450nm. Use at least 3 different coated glasses for testing, and test at least 3 absorbance data of the eluate of each glass. Perform significance analysis using Origin software, and then calculate the degradation rate.
[0194] Degradation rate of methyl orange / xylenol orange = (A 空白组 -A 实验组 ) / A 空白组 ×100%
[0195] (4) PCT High-Voltage Accelerated Aging Test: The uncoated organic coated glass to be tested is cut into 300×300 mm square pieces, and then placed vertically in a high-voltage accelerated aging test chamber with a 2-3 cm distance between the glass pieces. The test is then conducted continuously for 48 hours at a temperature of 121°C, a humidity of 100%, and 2 standard atmospheres. A pass indicates that the service life of the film layer is approximately 20 years.
[0196] Table 1 Test results
[0197]
[0198]
[0199] Note: Two groups of the same coated glass were used for coating organic matter and PCT accelerated aging. Comparative Examples 1 to 4 were used as blank groups for Examples 1 to 4, so the degradation rate relative to the blank group was 0. There was no significant difference between the degradation rate of xylenol orange in Comparative Example 6 and the blank group. The degradation rates of methyl orange / dimethyl orange were both low because the experiment used light irradiation simulating sunlight instead of ultraviolet irradiation. The degradation rate of xylenol orange was lower than that of methyl orange because the concentration of xylenol orange used was 10 times that of methyl orange.
[0200] Examples 1 to 4 all added TiO 2The transmittance of the film layer decreased by about 0.2% compared with that of Comparative Examples 1 to 4. However, after the organic coating test, the transmittance of Examples 1 to 4 did not change significantly, and the degradation rate of methyl orange was 15% and the degradation rate of xylenol orange was 4% compared with that of Comparative Examples 1 to 4, while the transmittance of the film layer of Comparative Examples 1 to 4 decreased by 0.3%, which indicates that the addition of TiO 2 After sol-gelling, the film layer can effectively degrade organic matter remaining on the surface, and at the same time make it difficult for it to remain on the surface of the film layer after pure water washing; PCT accelerated aging test results show that adding TiO 2 The weathering properties of the original coating solution will not be changed after sol-gel treatment, indicating that TiO 2 The sol has little impact on the original coating solution and has high compatibility.
[0201] The transmittance enhancement rate of comparative example 5 is low because the addition of TiO 2 Too much sol will form TiO 2 -SiO 2 The raspberry-like structure is too dense, which increases the refractive index of the film. The transmittance of comparative example 6 is also low because the amount of water in the ratio is too much, and TiO 2 The sol particle size is too large to form TiO 2 -SiO 2 The raspberry-like structure of the TiO2 reduces the performance of degrading organic matter. The transmittance enhancement rate of Comparative Example 7 is the lowest, but its degradation rate of methyl orange / xylenol orange is the highest because its tempering temperature is low and TiO2 2 The proportion of anatase type in the crystal form is higher, but the tempering temperature is low and the PCT accelerated aging of the film layer does not pass.
[0202] Finally, it should be noted that the rapid development of the photovoltaic industry has led to an oversaturation of solar photovoltaic module production capacity, and has gradually shifted from large-scale centralized distribution to small-scale decentralized layouts, such as building roofs, viaduct sound barriers, and solar roads. However, solid suspended particles on urban roads usually combine with hydrocarbons, nitrogen oxides, sulfur oxides, etc. emitted by automobile exhaust to form organic solid suspended particles. Photovoltaic modules that operate for a long time in such an environment usually accumulate a layer of powder formed by organic solid suspended particles on the surface, resulting in a significant decrease in the transmittance of the coated glass on the module. Due to the particularity of the solid particles, rainwater is difficult to effectively clean them, and organic matter remains on the surface of the coated glass. The photoelectric conversion efficiency of the module also decreases, seriously affecting the normal power generation of the module.
[0203] Nano-TiO formed by sol-gel method under acidic conditions 2 Sol is compatible with existing coating solutions on the market to form TiO 2 -SiO 2The coating liquid with a raspberry-like structure adds the ability to degrade organic matter to the film layer after the glass is tempered. After being washed by rain, it is difficult for organic matter to remain on the film surface, giving the photovoltaic glass surface a self-cleaning function. 2 The introduction of sol will not change the PCT weather resistance of the original film layer, and its stability and compatibility are good. It can keep the surface of photovoltaic glass clean after long-term use in an atmosphere of organic solid suspended particles, thereby reducing the maintenance cost of photovoltaic modules and maintaining stable power generation efficiency of the modules.
[0204] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A sol, characterized in that: Secondary particles are dispersed in the sol, and the secondary particles include a SiO2 microsphere matrix and TiO2 sol particles attached to the surface of the SiO2 microsphere matrix. The average particle size of the TiO2 sol particles is smaller than the average particle size of the SiO2 microsphere matrix.
2. The sol according to claim 1, characterized in that The average particle size of the secondary particles is 70nm to 80nm; and / or, the average particle size of the TiO2 sol particles is 15nm to 20nm; and / or, the average particle size of the SiO2 microsphere matrix is 40nm to 60nm.
3. A method for preparing the sol as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Premixing butyl titanate, a diluent and acetic acid to prepare liquid A; (2) mixing water and a diluent, and adding a pH adjuster to adjust the pH to obtain a solution B; (3) adding the liquid A dropwise to the stirred liquid B, and continuing the stirring reaction to obtain a nano-TiO2 sol; (4) The TiO2 sol and SiO2 coating solution are mixed to obtain the sol.
4. The method according to claim 3, characterized in that In step (1), the molar ratio of butyl titanate, diluent and acetic acid is 1:20-30:0.25-0.
75.
5. The method according to claim 3, characterized in that: In step (2), the mass ratio of the water to the diluent is 1:25-35; and / or the molar ratio of the water to the butyl titanate is 2-5:
1.
6. The method according to claim 3, characterized in that In step (2), the pH is adjusted to 2-3.
7. The method according to claim 3, characterized in that In step (3), the dropping speed is 2 to 4 s / drop; and / or the stirring reaction time is 3 to 5 h.
8. The method according to claim 3, characterized in that In step (4), the solid content ratio of the TiO2 sol to the SiO2 plating solution is 0.03-0.05:
1.
9. An organic degradation film, characterized in that: The sol is obtained by solidifying the sol according to any one of claims 1 to 2 or the sol prepared by the method according to any one of claims 3 to 8.
10. A photovoltaic glass, characterized in that: The surface of the photovoltaic glass is provided with the organic matter degradation film as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing high- stable neutral mixed crystal nanometer TiO2 hydrosol
CN101306838B
Preparation method and application of a titanium dioxide photocatalytic coating
CN104588021B
Nano-tio2 coating structure and preparation method and use thereof
CN106582892B